RESPOSTAS GERMINATIVAS DE LACTUCA SATIVA E UROCHLOA BRIZANTHA EXPOSTAS A SURFACTANTES CATIÔNICOS, ANIÔNICOS E NEUTROS. - FERNANDES, Simone Yasuda; ARAÚJO, Débora; SANTOS, Jaqueline Silva; PONTES, Montcharles Silva; ARRUDA, Gilberto; SANTIAGO, Etenaldo F. (ANAIS DO ENIC, 2023)
-